The impact of pest risk management measures on trade: The case of apples from France and Chile - Federica De Maria; Sophie Drogue; Pasquale Lubello (Agricultural and Food Economics, 2021)
In this article, we investigate how pest risk management protocols may affect trade flows of fresh apples. We apply our analysis to two major players in the international trade of fresh apples: France and Chile. These two countries have been chosen because they are among the world's leading apple exporters and although they have similar market shares, they differ in terms of destination markets, seasonality, local conditions and export strategy. In order to assess the impact of pest risk management protocols on international trade of apples from France and Chile, we introduce in a gravity equation beside the traditional variables, a score able to measure their complexity. The results are interesting in the sense that even if the score for France and Chile by main trading partners are rather close, we found that French apples exporters would be more impacted by pest risk management protocols than their Chilean counterparts.
Keywords: F13; Q17; 330; Apples; Chile; France; Gravity Modelling; International trade; SPS measures